1977
DOI: 10.2134/jeq1977.00472425000600020005x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Propanil, DCA, and TCAB in Soil and Water Under Flooded Rice Culture

Abstract: Field experiments were conducted to determine the residue levels of propanil (3′,4′‐dichloropropionanilide), DCA (3,4‐dichloroaniline), and TCAB (3,3′,4,4′‐tetrachloroazobenzene) in the flood water and Beaumont clay soil under normal rice (Oryza sativa L.) cultivation. Propanil applied as a foliar spray at 3.4 and 6.8 kg/ha 24 hours before flooding was dissipated from the flood water within 24 hours following the flood. The amount of propanil dissipated corresponded to the DCA concentration in the flood water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…Several surface water monitoring programmes have been carried out to quantify the degree of contamination by pesticides (Kammerbauer & Moncada, 1998;Huber et al, 2000;Kolpin et al, 2000;Bouman et al, 2002;Cerejeira et al, 2003;Martínez et al, 2003). Rice crop conducted under flooded conditions is pointed out as being an activity of high pollution potential (FEPAM, 2004). The factors that contribute to this claim are the large amount of water used to maintain the flood (Machado et al, 2006), the usual proximity of the fields to surface water bodies, the predominant shallow aquifer in these areas, and the intentional and unintentional release of water from the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surface water monitoring programmes have been carried out to quantify the degree of contamination by pesticides (Kammerbauer & Moncada, 1998;Huber et al, 2000;Kolpin et al, 2000;Bouman et al, 2002;Cerejeira et al, 2003;Martínez et al, 2003). Rice crop conducted under flooded conditions is pointed out as being an activity of high pollution potential (FEPAM, 2004). The factors that contribute to this claim are the large amount of water used to maintain the flood (Machado et al, 2006), the usual proximity of the fields to surface water bodies, the predominant shallow aquifer in these areas, and the intentional and unintentional release of water from the field.…”
Section: Introductionmentioning
confidence: 99%
“…Propanil is weakly adsorbed by the soil, is moderately mobile in sandy soils and of low mobility in clayey soils, with half-life of 1 to 3 days (Vencill, 2002). Studies on the persistence of propanil in irrigated rice conditions showed that its dissipation occurs within 24 hours and that the amount of dissipated propanil corresponds to the concentration of 3,4-dichloroaniline (DCA), indicating biological degradation of propanil to DCA (Deul et al, 1977). Quinclorac has variable mobility depending on soil type and organic matter and it can persist in the soil for one year affecting susceptible crops in rotation programs (Vencill, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pothuluri et al (1991) detailed the toxicology, metabolism, and fate of propanil in soil and water. Others researchers documented that propanil forms 3,4 DCA through enzymatic cleaving in plants (Adachi et al, 1966; Frear and Still, 1968), paddy field flooding waters (Deuel et al, 1977), and soils (Bartha, 1968; Bartha and Pramer, 1967; Bartha et al, 1968). A number of microorganisms, such as Pseudomonas spp., Fusarium solani , Athrobacter spp., Nocardia spp., and Consortia spp., have been shown to degrade propanil by microbial peroxidizes (Pothuluri et al, 1991) to the by‐product 3,3′,4,4′ tetrachloroazobenzene (TCAB) (Carey et al, 1980; Chisaka and Kearney, 1970; Pothuluri et al, 1991; Sprott and Corke, 1971).…”
mentioning
confidence: 99%
“…The 3,4-DCA is detected up until the second week after the application of propanil and on the 14 th day after the application the presence of 3,4-DCA was still detected at a concentration of 1.6 µg L -1 . Studies on the persistence of propanil in irrigated rice conditions conducted by Deul et al (1977) showed that its dissipation occurs within 24 hours and that the amount of dissipated propanil corresponds to the concentration of 3,4-dichloroaniline (DCA), indicating biological degradation of propanil to DCA.…”
Section: Wwwintechopencommentioning
confidence: 99%